(untitled) - Elmasri, Ramez (Reading, Mass., 2000)
Fundamentals of Database Systems combines clear explanations of theory and design, broad coverage of models and real systems, and excellent examples with up-to-date introductions to modern database technologies. This edition is completely revised and updated, and reflects the latest trends in technological and application development. Professors Elmasri and Navathe focus on the relational model and include coverage of recent object-oriented developments. They also address advanced modeling and system enhancements in the areas of active databases, temporal and spatial databases, and multimedia information systems. This edition also surveys the latest application areas of data warehousing, data mining, web databases, digital libraries, GIS, and genome databases.
Cơ sở dữ liệu nâng cao
Keywords: Database management